A linguagem do blog escolar em um trabalho com multiletramentos: compartilhando sentidos - Griner, Ana Priscila (2013)
This research, part of Applied Linguistics field, aims to analyze the language of a school blog, developed with the participation of students, as a work based on the conception of multiliteracies, focusing on the construction of different meanings. The research is carried on from the building and maintenance of a school blog, the Ieceblog, with students of Ensino Fundamental II, since 2008, in a private school in Natal-RN. The investigation of the language produced on a school blog is justified due to the interactive conceptions of writing and reading on the virtual environment. Given the fact that new technologies are a reality in the schools opened to the practices of multiliteracies, it is assumed that text, image, video, audio, non-graphic signs and hypertext intensifies the produced interaction, in which the students become real authors. In this perspective, some voices belonging to the statements that are formed through the posts and comments chosen to the analyses and reflection on the blog space as locus of productions of senses inserted in the school and the world environment, as well as for the identification of the language resources used to intensify the senses that emerge from it. From the view of dialogism conceptualized by Bakhtin Circle, the qualitative interpretive-research deepens the experience of a school blog focusing on digital language in line with the vision of digital literacy. From the blog posts, a corpus that promote the exposure of different manifestations of language in the design of digital multiliteracies is elected. Thereby, the method used was the dialogical analysis of speech based on Bakhtin s studies and the Circle. The corpus was taken from the blog s posts in order to point up the different language manifestations in the following categories: (i) mood reinforced by the mockery, (ii) search for compliance with school sphere, (iii) conflicting social values and consistent complicity between sense and verbal imagery, and finally (iv) social practices that take place from and through the discursive genre. The study points to the tension between the active voices in several directions, revealing the distorted unit of posts which, under the analytical observation raises multiple meanings in a responsive manner. The analysis of the dialogue interaction in which intersperses the digital one becomes more apparent that the multiliteracies events that are mediated by language in addition to structure of the language and makes us rethink the students